Doing More with Less: Surgical Training in the COVID-19 Era. Issue 1 (2nd January 2022) - Doulias, Triantafyllos; Gallo, Gaetano; Rubio-Perez, Ines; Breukink, Stephanie O.; Hahnloser, Dieter
Abstract: Background: The impact of COVID-19 in healthcare systems globally was unprecedented leading to cancelations of most planned surgical activities. Surgical trainees were redeployed to Intensive Care and Emergency units supporting urgent and unplanned care on COVID-19 patients. Theater exposure, crucial part of surgical training, was reduced to minimal since elective cases were postponed, and emergency operating was carried out by consultants only. Surgical research has also been severely hit with most of the clinical trials been postponed. Teaching activities as well as national and international congresses and surgical courses important tools for continuous professional development were canceled. Methods: The primary aim of our study was to summarize the changes in surgical training during the pandemic. This was followed by a review of the existing social media platforms, video-conferencing platforms along with the role of the social media in surgical training. The crucial role of simulation in surgical training was explored and alternative ways of training with engagement of the feedback mechanisms were proposed. The secondary aim was to highlight possible novel educational strategies for the forthcoming post-COVID-19 era. Conclusions: The "new" era forced the educational boards to reexamine training curriculums. Innovation strategies and cooperation on the part of surgical residency programs is crucial. Strong leadership is needed, on the part of the education bodies with restructuring of the surgical programmes to accommodate alternative ways of training is necessary to maintain rigorous standards of education and training.